Business Sector Financial Performance Evaluation Using Automated Approach in Assisting Investors’ Decision-Making - Abdul Rahim, Siti Khatijah Nor; Jaafar, Amir Hamzah; Karim, Hilwana Abdul; Rahim, Zati Halwani Abdul; Azhar, Farah Waheeda; Fahami, Norasyikin Abdullah (Technium Social Sciences Journal, 2023)
Investors must carefully study and analyze a company’s financial performance in order to avoid the risk of financial losses, which takes a lot of time due to the numerous criteria or financial statistics that must be taken into account. The investor’s choice of the best company to invest in is further complicated by the limitations of human reasoning when faced with a large selection of choices. This study has proposed an automated system to help investors who plan to make investments by offering features to assess the financial performance of particular businesses within particular industries. The authors have suggested two strategies: TOPSIS and Fuzzy Logic approaches. Successful automated system development has been accomplished using these approaches. The approach allows investors the freedom to select from a range of performance evaluation criteria to establish the rankings. Investors can view the companies’ rank in terms of their financial performance. Investors may also avoid getting overwhelmed with complicated, perhaps conflicting web information by employing the existing systems. It is observed that the proposed system is very user-friendly and managed to assist the investors’ decision-making in making investments. It should be noted that the developed systems can be useful not only to investors but also to students taking business courses. From our analysis, there is no just one right technique to analyze a company and assess its current standings. Therefore, in the future, we recommend introducing an aggregate method to business appraisal in order to further give potential investors a better depiction of the businesses.